2006
DOI: 10.1098/rsbl.2006.0509
|View full text |Cite
|
Sign up to set email alerts
|

Cues of being watched enhance cooperation in a real-world setting

Abstract: We examined the effect of an image of a pair of eyes on contributions to an honesty box used to collect money for drinks in a university coffee room. People paid nearly three times as much for their drinks when eyes were displayed rather than a control image. This finding provides the first evidence from a naturalistic setting of the importance of cues of being watched, and hence reputational concerns, on human cooperative behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
705
7
16

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,012 publications
(757 citation statements)
references
References 16 publications
29
705
7
16
Order By: Relevance
“…The fact that people might change their behavior simply because they are being observed has been documented in other fields as well, and has been attributed to reputational concerns (e.g. Bateson et al, 2006). Thus, it seems plausible that, in addition to seasonal changes in weather and traffic conditions, increased speeding from pre-to post-measurement can be attributed to the fading awareness of being monitored.…”
Section: Effects Of Being Monitoredmentioning
confidence: 97%
“…The fact that people might change their behavior simply because they are being observed has been documented in other fields as well, and has been attributed to reputational concerns (e.g. Bateson et al, 2006). Thus, it seems plausible that, in addition to seasonal changes in weather and traffic conditions, increased speeding from pre-to post-measurement can be attributed to the fading awareness of being monitored.…”
Section: Effects Of Being Monitoredmentioning
confidence: 97%
“…This alertness can misfire: it has been shown that by merely seeing the image of an eye, players can be motivated to increase donations substantially [56][57][58]. Such obvious maladaptions strongly support the hypothesis that our evolutionary legacy shapes our economic behaviour.…”
Section: Proximate Causes Of Costly Punishmentmentioning
confidence: 98%
“…Research in this area has shown that individuals pay nearly three times more for drinks when a pair of eyes were placed on a donationbased vending machine then when images of flowers were placed on the machine (Bateson, Nettle, and Roberts 2006). Similarly, people contribute more in public-goods games when they see images of a robot on their computer screen (Burnham and Hare 2007) or when a pair of schematic eyes are placed in their computer background (Haley and Fessler 2005).…”
Section: What Key Outcomes?mentioning
confidence: 99%
“…Attention evoked by embodied cues can also affect economic decisions (Haley and Fessler 2005;Bateson, Nettle, and Roberts 2006;Burnham and Hare 2007). Research in this area has shown that individuals pay nearly three times more for drinks when a pair of eyes were placed on a donationbased vending machine then when images of flowers were placed on the machine (Bateson, Nettle, and Roberts 2006).…”
Section: What Key Outcomes?mentioning
confidence: 99%